SALES FORCE ALLOCATION IN BANKING SECTOR - BULKAN, SEROL (My University, 2018)
Sales force deployment involves the simultaneous resolution of interrelated sub-problems like sales forcesizing, sales representative location, sales territory alignment, and sales resource allocation. As the sales forcesize increases, the number of accounts to be visited increases that yields to a positive effect on sales rates butalso an increase in operational costs. Therefore, the alignment decisions are vital for all issues such as thenumber of outbound calls to accounts, the operational expenses, and the sales representative asset (time) thatmight be allocated. All sub-problems have to be resolved in order to maximize the profit of the sellingorganization. In this paper, sales force allocation problems in the literature are examined and approaches tosimilar problems are compared. A non-linear mixed-integer quadratic programming model is formulated forsales force allocation in banking sector. And a heuristic approach is developed for big size problems. Thecomparison of approaches is reported.

Satış gücü yerleştirme problemleri; satış gücü sayısı belirleme, satışçıların yerleştirilmesi, satış alanının belirlenmesi ve satış kaynağının yerlerinin belirlenmesi olarak alt problemlerle bağlantılıdır. Satış gücünün büyüklüğü arttıkça, ziyaret edilecek lokasyon sayısı artar ve satışlar olumlu yönde etkilenir. Öte yandan, satış gücünün arttırılması işletme maliyetlerini arttırılmasına yol açar. Bu sebeple, ziyaret edilecek lokasyon sayıları, operasyonel maliyetler ve satış gücü(saat) yerleştirmesi çok önemlidir. Organizasyonlarda bu alt problemler kar maksimizasyonu yaklaşımıyla çözülmektedir. Literatürdeki satış gücü yerleştirme problemleri incelenmiş, benzer problemlere yaklaşımlar karşılaştırılmıştır. Bu çalışmada banka sektöründeki satış gücü yerleştirmesi için doğrusal olmayan karmaşık tam sayı programlama modeli oluşturulmuştur. Problemin büyük olabileceği durumlar için alternatif sezgisel model yaklaşımı yapılmıştır. Bu makalede de bu yaklaşımlar karşılaştırılıp raporlanmıştır.
BANKACILIK SEKTÖRÜNDE SATIŞ GÜCÜ YERLEŞTİRME